Influence of Structural Defects and Oxidation onto Hole Conductivity in P3HT - Lücke, A.; Schmidt, Wolf Gero; Rauls, E.; Ortmann, F.; Gerstmann, Uwe (The Journal of Physical Chemistry B)

Barrier-free subsurface incorporation of 3d metal atoms into Bi(111) films - Klein, C.; Vollmers, N. J.; Gerstmann, Uwe; Zahl, P.; Lükermann, D.; Jnawali, G.; Pfnür, H.; Tegenkamp, C.; Sutter, P.; Schmidt, Wolf Gero; Horn-von Hoegen, M. (Physical Review B)

Structure formation in diindenoperylene thin films on copper(111) - Aldahhak, Hazem; Matencio, S.; Barrena, E.; Ocal, C.; Schmidt, Wolf Gero; Rauls, E. (Physical Chemistry Chemical Physics)
First-principles calculations were combined with scanning tunneling microscopy (STM) measurements to analyze the adsorption of diindenoperylene (DIP) molecules on Cu(111) surfaces.

Modeling atomic force microscopy at LiNbO 3 surfaces from first-principles - Sanna, S.; Dues, C.; Schmidt, Wolf Gero (Computational Materials Science)

Structure formation in diindenoperylene thin films on copper(111) - Aldahhak, Hazem; Matencio, S.; Barrena, E.; Ocal, C.; Schmidt, Wolf Gero; Rauls, E. (Physical Chemistry Chemical Physics)
First-principles calculations were combined with scanning tunneling microscopy (STM) measurements to analyze the adsorption of diindenoperylene (DIP) molecules on Cu(111) surfaces.

Polaronic deformation at theFe2+/3+impurity site inFe:LiNbO3crystals - Sanson, A.; Zaltron, A.; Argiolas, N.; Sada, C.; Bazzan, M.; Schmidt, Wolf Gero; Sanna, S. (Physical Review B)

GaNm-plane: Atomic structure, surface bands, and optical response - Landmann, M.; Rauls, E.; Schmidt, Wolf Gero; Neumann, M. D.; Speiser, E.; Esser, N. (Physical Review B)

Sustaining Civil Peace: A Configurational Comparative Analysis - Gries, Thomas; Palnau, Irene (Peace Economics, Peace Science and Public Policy)

Does technological change drive inclusive industrialization? A review of major concepts and findings - Gries, Thomas; Grundmann, Rainer; Palnau, Irene; Redlin, Margarete

A panel of peralkylated sulfur–guanidine type bases: Novel pro-ligands for use in biomimetic coordination chemistry - Neuba, Adam; Rohrmüller, Martin; Hölscher, Rebecca; Schmidt, Wolf Gero; Henkel, Gerald (Inorganica Chimica Acta)

Towards 100 Gbps Wireless Communication in THz Band with PSSS Modulation: A Promising Hardware in the Loop Experiment - KrishneGowda, Karthik; Messinger, Tobias; Wolf, Andreas; Kraemer, Rolf; Kallfass, Ingmar; Scheytt, Christoph (ICUWB 2015)
Terahertz frequency band of 0.06 - 10 THz is especially interesting for ultra-high-speed wireless communication to achieve data rates of 100 Gbps or higher. To accommodate this demand, advanced terahertz signal processing techniques need to be investigated. Parallel Sequence Spread Spectrum (PSSS) is a physical layer (PHY) baseband technology that seems to be suited for being used for ultra-high speed wireless communication since the receiver architecture is especially simple and can be implemented almost completely in analog hardware. In this paper, a PSSS modulated signal at a chip rate of 20 Gcps with a spectral efficiency of (only) 1 bit/s/Hz is transmitted using a linearity limited 240 GHz wireless frontend. PSSS transceiver models are realized offline in MATLAB/Simulink. The PSSS transmitter generates the PSSS modulated symbols that are loaded onto an Arbitrary Waveform generator (AWG) and then transmitted using the available 240 GHz wireless frontend. A Digital Storage Oscilloscope (DSO) samples and stores the received signal. The PSSS receiver performs synchronization, channel estimation and demodulation. For a coded data rate of 20 Gbps, an eye opening of 40% and a BER of 5.4·10 -5 has been measured. These results are highly promising to achieve data rates of up to 100 Gbps with PSSS modulation using a RF-frontend having higher linear operating range and thus allowing increasing the bandwidth efficiency to 4 b/s/Hz.

Shifting the Analog-Digital Boundary in Signal Processing: Should We Use Mixed-Signal "Approximate" Computing? - Scheytt, Christoph; Javed, Abdul Rehman (Workshop on Approximate Computing)

Analyse von Ausführungszeiten durch Integration einer statischen WCET-Analyse mit einer dynamischen Befehlssatzsimulation am Beispiel der TriCore-Architektur - Adelt, Peer

Miniaturized 122 GHz ISM Band FMCW Radar with Micrometer Accuracy - Scherr, Steffen; Göttel, Benjamin; Ayhan, Serdal; Bhutani, Akanksha; Pauli, Mario; Winkler, Wolfgang; Scheytt, Christoph; Zwick, Thomas (European Microwave Week 2015)
In this paper, a miniaturized 122 GHz ISM band FMCW radar is used to achieve micrometer accuracy. The radar consists of a SiGe single chip radar sensor and LCP off-chip antennas. The antennas are integrated in a QFN package. To increase the gain of the radar, an additional lens is used. A combined frequency and phase evaluation algorithm provides micrometer accuracy. The influence of the lens phase center on the beat frequency phase and hence, the overall accuracy is shown. Furthermore, accuracy limitations of the radar system over larger measurement distances are investigated. Accuracies of 200 μm and 2 μm are achieved over a distance of 1.9 m and 5 mm, respectively.

On the Correlation of HW Faults and SW Errors - Müller, Wolfgang; Wu, Liang; Scheytt, Christoph; Becker, Markus; Schoenberg, Sven (Proceedings of the 1st International Workshop on Resiliency in Embedded Electronic Systems (REES 2014))

Integrated Planar Antenna Designs and Technologies for Millimeter-Wave Applications - Wang, Ruoyu
This thesis investigates the design and realization of integrated planar antennas for millimeter-wave applications. The state-of-the-art antenna integration and packaging technologies are extensively studied, and an antenna design flow is proposed. A number of integrated antenna designs by applying different integration approaches and technologies, i.e. on printed circuit board (PCB), on-chip and in Benzocyclobutene (BCB) above-wafer process, are presented. The designs target not only high performance, but also the practical considerations of low-cost, feasibility, better reliability, and good reproducibility. They cover the industrial, medical, and scientific (ISM) bands of 60 GHz, 122 GHz, and 245 GHz in the millimeter-wave range with outstanding performance in a low-cost fashion by applying innovative, appropriate integration methods and sophisticated design. By applying the localized backside etching (LBE) process the presented on-chip antennas achieve measured peak gains of 6–8.4 dBi for above 100 GHz applications with simulated efficiencies of 54–75%. These figures are comparable to that of on-board or in-package antennas. To the best of my knowledge, the achieved gain of 7.5–8.4 dBi in the band of 124–134 GHz for the 130 GHz on-chip double folded dipole antenna is the highest reported result to date for planar on-chip antennas based on low-resistivity silicon technologies. System demonstrators with integrated antennas are realized and measured. The 60 GHz demonstrator with on-PCB differential bunny-ear antenna and a novel bond-wire compensation scheme achieves a data rate of 3.6 Gbit/s over a 15-meter distance, which was the best reported analog front-end without beamforming function in silicon technology regarding both the data rate and transmission distance at the time of its publication. A 245 GHz single-channel transmitter and a single-channel receiver with integrated on-chip antennas are also demonstrated. An effective isotropic radiated power (EIRP) of 7–8 dBm is achieved for the transmitter, which is the highest reported value at 245 GHz for a SiGe transmitter with a single antenna so far. Furthermore, the receiver has the highest reported integration level for any 245 GHz SiGe receiver. A 245 GHz 4-channel-transmitter array with integrated on-chip antenna array is also realized to achieve spatial power combining, which offers 11 dB higher EIRP than a single-channel transmitter. From the presented results of the thesis it is feasible to realize high performance integrated planar antennas in the entire millimeter-wave range and beyond in a cost-effective fashion.

System Design Considerations for a PSSS transceiver for 100Gbps wireless communication with emphasis on mixed Signal implementation - Javed, Abdul Rehman; Scheytt, Christoph; KrishneGowda, Karthik; Kraemer, Rolf (Wireless and Microwave Technology Conference (WAMICON))
Parallel Sequence Spread Spectrum (PSSS) is a physical layer (PHY) baseband technology which is gaining interest for both wireless and wired multi-gigabit communication systems. PSSS is well suited for mixed signal transceiver implementation including channel equalization and allows for a reduction in power dissipation by avoiding high speed data converters. The architecture of a mixed signal baseband processor for 100 Gbps wireless communication is described that reduces the implementation complexity and results in a consequent reduction in power dissipation and chip area.

System Design and Simulation of a PSSS Based Mixed Signal Transceiver for a 20 Gbps Bandwidth Limited Communication Link - Javed, Abdul Rehman; Scheytt, Christoph (1st URSI Atlantic Radio Science Conference (URSI AT-RASC 2015))
Parallel Sequence Spread Spectrum (PSSS) is a physical layer baseband technology wherein parallel data streams are transmitted simultaneously by spreading them using orthogonal codes. PSSS was selected for the wireless sensor network standard IEEE802.15.4-2006 to increase data rate and improve performance in fading channels for frequency bands below 1 GHz. Since then it has gained interest for both wireless and wired communication links.

Mixed-Signal Baseband Processing for 100 Gbit/s Communications - Scheytt, Christoph; Javed, Abdul Rehman (European Microwave Week 2015)

Mixed-mode Baseband for 100 Gbit/s Wireless Communications - Javed, Abdul Rehman; Scheytt, Christoph; Kraemer, Rolf; Messinger, Tobias; Kallfass, Ingmar